2011
DOI: 10.1097/pcc.0b013e3181e2a244
|View full text |Cite
|
Sign up to set email alerts
|

Emergency tracheal intubation of severely head-injured children: Changing daily practice after implementation of national guidelines*

Abstract: Scene emergency tracheal intubation was effectively performed by trained careproviders in children with traumatic brain injury. Implementation of guidelines led to a more standardized practice of RSI, decreased rate of immediate complications, but insufficient control of Paco2 during transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 31 publications
1
12
0
2
Order By: Relevance
“…Our result is in agreement with those reported by Martinon et al [8] from Paris who found that the prevalence of automated ventilator use following RSI on paediatric TBI patients rose to 88% after the implementation of their guideline. Our result compares favourably to those found by Bosse et al [5] and Francis et al [6] from the physician-staffed EMS in Berlin.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our result is in agreement with those reported by Martinon et al [8] from Paris who found that the prevalence of automated ventilator use following RSI on paediatric TBI patients rose to 88% after the implementation of their guideline. Our result compares favourably to those found by Bosse et al [5] and Francis et al [6] from the physician-staffed EMS in Berlin.…”
Section: Discussionsupporting
confidence: 94%
“…The same research group also found that introducing an SOP for patient documentation did improve the quality of the patient care reports [7]. Martinon et al from the physician-staffed Service d’Aide Médicale Urgente (SAMU) in Paris reported that the implementation of an SOP for pre-hospital rapid sequence intubation (RSI) and post-RSI treatment of children with severe traumatic brain injury (TBI) significantly improved quality of care on several, but not all quality indicators [8]. Hejselbaek et al from the anaesthesiologist-staffed EMS in Copenhagen reported difficulties in getting pre-hospital critical care anaesthesiologists to follow clinical guidelines for the pre-hospital use of hypertonic saline [9].…”
Section: Introductionmentioning
confidence: 99%
“…Es ist jedoch unbestritten, dass aufgrund der niedrigen Fallzahl von präklinischen Säuglings-oder Kinderintubationen die notwendige Expertise nicht allein in der notfallmedizinischen Praxis erworben werden kann [1,9]. Demnach erlangt das Thema des alternativen Atemwegsmanagements für Rettungsdienstpersonal, Notärzte und innerklinische Erstversorger von lebensbedrohlichen Kindernotfällen eine zunehmende Bedeutung [17,20,22].…”
unclassified
“…Multiple other studies have indicated that airway PHIs have been detrimental to mortality and functional outcome when compared with manual bag mask ventilation. 3,9,33 DiRusso et al retrospectively studied intubation in 50,199 pediatric trauma patients and found that PH intubation was associated with significantly higher death rates when compared with intubation in an ED setting. Moreover, multiple other studies have suggested that PHI-As in the setting of pediatric TBIs may be associated with adverse outcomes.…”
Section: Discussionmentioning
confidence: 97%